2014
DOI: 10.1088/0741-3335/56/9/095030
|View full text |Cite
|
Sign up to set email alerts
|

Confinement degradation by Alfvén-eigenmode induced fast-ion transport in steady-state scenario discharges

Abstract: Analysis of neutron and fast-ion D α data from the DIII-D tokamak shows that Alfvén eigenmode activity degrades fast-ion confinement in many high β N , high q min , steady-state scenario discharges. (β N is the normalized plasma pressure and q min is the minimum value of the plasma safety factor.) Fast-ion diagnostics that are sensitive to the co-passing population exhibit the largest reduction relative to classical predictions. The increased fast-ion transport in discharges with strong AE activity accounts fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 48 publications
6
63
1
2
Order By: Relevance
“…14 Conditions with multiple unstable AEs occur both in L-mode plasmas during the current ramp 6,14,25 and in H-mode steady-state scenario plasmas with elevated q profiles. 26,27 Fast-ion diagnostics include the volume-averaged neutron rate, 28 which is dominated by beam-plasma reactions in the L-mode plasmas, FIDA diagnostics with oblique sightlines, 29 and solid-state neutral-particle analyzers (NPA) operated in current mode 30 (Fig. 2).…”
Section: Critical Gradient Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…14 Conditions with multiple unstable AEs occur both in L-mode plasmas during the current ramp 6,14,25 and in H-mode steady-state scenario plasmas with elevated q profiles. 26,27 Fast-ion diagnostics include the volume-averaged neutron rate, 28 which is dominated by beam-plasma reactions in the L-mode plasmas, FIDA diagnostics with oblique sightlines, 29 and solid-state neutral-particle analyzers (NPA) operated in current mode 30 (Fig. 2).…”
Section: Critical Gradient Behaviormentioning
confidence: 99%
“…Figure 4 of Ref. 26 shows a pair of successive discharges, one with modest AE activity and the other with strong AE activity. The fast-ion measurements in the discharge with modest AE activity is consistent within experimental errors with classically predicted FIDA, neutron, and fast-ion stored energy signals, but the discharge with strong AE activity exhibits strong deviations on all fastion signals.…”
Section: Critical Gradient Behaviormentioning
confidence: 99%
“…At relatively low plasma current and large NBI power, the compound losses from classical (due to large orbits) and anomalous [due to Alfvén eigenmodes (AEs) and possibly other instabilities] effects can be significant and can lead to overheating and damage of the limiter tiles. However, recent detailed analysis [27] has shown that the anomalous fast ion losses are high mostly during the β N and density ramp-up phase, i.e. when the NBI power has increased significantly but the density has not yet reached flattop.…”
Section: Mhd Stability Limits and Fast Ion Lossesmentioning
confidence: 99%
“…During the steady-state phase of neutral beam heated DIII-D discharges with high > q 2 min ( ) and high poloidal β larger than two [1] a rich spectrum of Alfvén eigenmodes (AEs) is observed on multiple diagnostics such as the CO 2 interferometer as can be seen in figures 1(a) and 2(a). The AEs appear in the Doppler-shifted toroidicity and ellipticity induced frequency gaps and therefore identified as TAEs and EAEs.…”
Section: Introductionmentioning
confidence: 96%
“…The AEs appear in the Doppler-shifted toroidicity and ellipticity induced frequency gaps and therefore identified as TAEs and EAEs. When the AEs are present the measured neutron rate can be up to 40% lower than the classically expected neutron rate [2]. The classical neutron rate is based on fast-ion transport due to slowing-down and pitch angle scattering processes and is usually obtained from the TRANSP code [3].…”
Section: Introductionmentioning
confidence: 99%